Paleoproductivity proxies and alkenone precursors in the Western Mediterranean during the Early-Middle Pleistocene transition - Marino, Maria (2022)
Multidisciplinary analyses (taxonomic analysis of coccolithophore assemblages, stable oxygen isotopes, marine and terrestrial biomarkers) have been carried out on sediments from Ocean Drilling Program Site 975 in the Algero-Balearic basin, through late marine isotope stage (MIS) 20-19 (800-756 ka). The aim is to compare coccolithophore paleoproductivity proxies, such as C-37 alkenone concentration and nannofossil accumulation rate (NAR), and understand their relationship with paleoceanographic condition and paleoenvironmental changes, alkenone-producing precursors and unsaturated C-37 alkenone compounds. The patterns of C-37 alkenones and NAR provide reliable information on past paleoproductivity changes since coccolith dissolution and organic matter preservation were excluded as relevant processes at the site. This is testified by the high values of Nannofossil Dissolution Index and relation between C-37 alkenone concentration and Alcohol Preservation Index, the latter used as a proxy of sea bottom ventilation in the basin. A weak mismatching between NAR and C-37 alkenone concentration records has been observed and related to paleoenvironmental factors and ecological preferences of alkenone-producing species. Temperature variations mostly controlled the alternating interspecific abundance variations of these taxa through glacial-interglacial and stadial-interstadial climate phases. The percentage abundances of alkenone-producing species, Gephyrocapsa caribbeanica and Gephyrocapsa with open central area (mainly G. margerelii-G. muellerae) strongly co-varied with the percentages of C-37:2 and C-37:3, respectively during warm and cool-cold periods, suggesting their prominent role in producing these unsaturated C-37 alkenone compounds. Moreover, Gephyrocapsa spp. with open central area > 3 mu m were likely the main C-37:4 producers during the colder late MIS 20 stadial and stadial phases. Other factors in addition to temperature influenced the paleoproductivity proxy patterns. The oceanographic condition established during MIS 20-MIS 19 deglaciation and the more nutrient-rich surface waters during the orbitally-controlled organic-rich layer deposition in the early MIS 19 enhanced primary productivity leading to higher production and preservation of total C-37 alkenones.